Development of porous PCL-based microcarrier - Mohd. Salleh, Hamzah; Hashim, Yumi Zuhanis Has-Yun; Samsudin, Nurhusna; Abdul Halim, Muhammad A. N. (International Institute for Halal research and Training (INHART), IIUM, 2018)
Polycaprolactone (PCL) has been used for cell cultivation due to its biocompatibility. However, fabrication of porous PCL microcarrier was an obstacle and study of its biodegradability is also limited. In the present study, PCL-based porous microcarrier was fabricated with different parameters by using emulsion evaporation method. From the study, at 20% camphene concentration, optimum pore size was generated which was at 11.738 μm. During the fabrication of the microcarrier, most of the parameters showed effect on the size of the microcarrier. Under the biodegradability test, it showed that the porous structure of the microcarrier enhance the degradation rate of the microcarrier. Throughout the study, all the parameters tested for the fabrication of microcarrier showed effect on it and the porous structure improve the degradation rate of PCL microcarrier.